Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 35th International ACM SIGIR Conference on Research and Development in Information Retrieval 2012
DOI: 10.1145/2348283.2348332
|View full text |Cite
|
Sign up to set email alerts
|

Efficient query recommendations in the long tail via center-piece subgraphs

Abstract: We present a recommendation method based on the wellknown concept of center-piece subgraph, that allows for the time/space efficient generation of suggestions also for rare, i.e., long-tail queries. Our method is scalable with respect to both the size of datasets from which the model is computed and the heavy workloads that current web search engines have to deal with. Basically, we relate terms contained into queries with highly correlated queries in a query-flow graph. This enables a novel recommendation gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…To increase the speed of our recommendation, we only stored the 100,000 top scoring random walk results for each term. Bonchi et al [3] found this to have no or very limited effects on performance when used with c = 0.1.…”
Section: Technical Detailsmentioning
confidence: 98%
See 4 more Smart Citations
“…To increase the speed of our recommendation, we only stored the 100,000 top scoring random walk results for each term. Bonchi et al [3] found this to have no or very limited effects on performance when used with c = 0.1.…”
Section: Technical Detailsmentioning
confidence: 98%
“…We only consider one query recommendation algorithm based largely on the query flow graph (QFG) work of Boldi et al [2] and the term-query graph (TQGraph) work of Bonchi et al [3]. We use a query flow graph G in which the vertices V are queries from a query log L and the edges E represent reformulation probabilities.…”
Section: Query Recommendationmentioning
confidence: 99%
See 3 more Smart Citations